Upaya Peningkatan Kualitas Remaja Melalui Sosialisasi Kesehatan Reproduksi Remaja Terintegrasi Dengan Metode Peer Group Di Sma Negeri 1 Getasan Kabupaten Semarang - Sintikhewati Yeni Sucipto; Lisa Dwi Astuti (Pelita Abdi Masyarakat, 2022)
Background: Adolescence is a period that is very vulnerable to engaging in risky sexual and adolescent acquaintance behavior. Adolescent problems are still very complex and have a very detrimental impact on adolescents themselves. One of the factors that make teenagers involved in this problem is the low level of adolescent knowledge about reproductive health and the impact of risky behavior, including in SMA Negeri 1 Getasan. Method : Through community service activities in the form of socialization efforts with the peer group method, it is hoped that it can increase adolescent knowledge about reproductive health which can influence adolescent attitudes and behavior to avoid risky behavior. Result: The result after this socialization effort was an increase in knowledge about integrated adolescent reproductive health. Conlussion: The peer group method is one of the most effective methods in providing health information to the youth target group.